The data journalism handbook - Gray, Jonathan; Bounegru, Liliana; Chambers, Lucy (Theory in practice (Sebastopol, Calif.), 2012)
This title is a reference book that seeks to teach journalists and would-be journalists the importance and use of data to improve stories.